2018
DOI: 10.1097/jnr.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Family-Based Education on the Quality of Life of Persons With Type 2 Diabetes: A Randomized Clinical Trial

Abstract: Educating the families of patients was shown in this study to improve the QOL of the patient. The design of educational programs for nursing students must emphasize the role of the family in the care of chronic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…Other clinical outcomes reported to be expected in the patient were controlled blood pressure ( 22 , 26 , 30 - 35 ), controlled FBG ( 34 , 36 ), body mass index (BMI) ( 26 , 30 , 31 , 34 , 35 ); low-density lipoprotein (LDL) ( 22 , 36 ), high-density lipoprotein (HDL) ( 22 ), and total cholesterol ( 31 ). Some studies have also reported secondary outcomes, including patients’ knowledge ( 20 , 21 , 24 , 30 , 34 , 37 , 38 ), self-efficacy ( 21 , 22 , 24 , 34 , 36 , 39 - 41 ), habits ( 20 , 42 , 43 ), physical activity ( 22 , 24 , 34 , 40 , 41 ), ability to follow the diet ( 20 , 22 , 34 , 44 , 45 ), smoking ( 21 , 45 ), changes in medical treatment ( 31 , 35 , 42 , 44 , 46 ), self-management support ( 38 , 44 , 47 - 49 ), waist circumference ( 30 - 32 ), and healthy behavior ( 20 , 21 , 2...…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Other clinical outcomes reported to be expected in the patient were controlled blood pressure ( 22 , 26 , 30 - 35 ), controlled FBG ( 34 , 36 ), body mass index (BMI) ( 26 , 30 , 31 , 34 , 35 ); low-density lipoprotein (LDL) ( 22 , 36 ), high-density lipoprotein (HDL) ( 22 ), and total cholesterol ( 31 ). Some studies have also reported secondary outcomes, including patients’ knowledge ( 20 , 21 , 24 , 30 , 34 , 37 , 38 ), self-efficacy ( 21 , 22 , 24 , 34 , 36 , 39 - 41 ), habits ( 20 , 42 , 43 ), physical activity ( 22 , 24 , 34 , 40 , 41 ), ability to follow the diet ( 20 , 22 , 34 , 44 , 45 ), smoking ( 21 , 45 ), changes in medical treatment ( 31 , 35 , 42 , 44 , 46 ), self-management support ( 38 , 44 , 47 - 49 ), waist circumference ( 30 - 32 ), and healthy behavior ( 20 , 21 , 2...…”
Section: Resultsmentioning
confidence: 95%
“…Overall, the primary outcome included HbA1c and the quality of life of patients with T2DM. Other clinical outcomes reported to be expected in the patient were controlled blood pressure (22,26,(30)(31)(32)(33)(34)(35), controlled FBG (34,36), body mass index (BMI) (26,30,31,34,35); lowdensity lipoprotein (LDL) (22,36), high-density lipoprotein (HDL) (22), and total cholesterol (31). Some studies have also reported secondary outcomes, including patients' knowledge (20,21,24,30,34,37,38), self-efficacy (21,22,24,34,36,(39)(40)(41), habits (20,42,43), physical activity (22,24,34,40,41), ability to follow the diet (20,22,34,44,45), smoking…”
Section: Resultsmentioning
confidence: 99%
“…One study in Western countries found that patients thought allied healthcare workers were better able to understand their needs and concerns since they had more time available instead of the limited time with a clinician. 15 , 24 Patients in India found it easier to access their family physician versus dietitians, and were highly likely to follow a suggested diet plan. 15 , 25 In Nepal, community- and mid-level health facilities are often ill equipped to provide screening and treatment services for diabetes, thus forcing patients to attend less accessible, higher-level health facilities.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 24 Patients in India found it easier to access their family physician versus dietitians, and were highly likely to follow a suggested diet plan. 15 , 25 In Nepal, community- and mid-level health facilities are often ill equipped to provide screening and treatment services for diabetes, thus forcing patients to attend less accessible, higher-level health facilities. Hence one method gaining attention in a growing number of low-resource settings is the use of community-based programs to supplement hospital-based services for chronic diseases such as diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation